Relationship between Demographic and Employment Parameters with Job Stress Among Employees of an Oil Field in Western Iran - Askari, Ali; Borjaki, Jabar; Mahdinasab, Laila; Abadi, Ali Salehi Sahl (Universitas Ahmad Dahlan, 2023)
Reducing the workforce's health condition is one of the significant challenges in industries. Various studies have shown that efficiency in industries has a crucial relationship with the workforce's health level. In addition, the employee's health can be affected by different variables such as stress or other job parameters and the type of work system. The present study was conducted to analyze the relationship between these parameters and job stress in an oil field. This work was a cross-sectional and descriptive-analytic investigation. The statistical population included workers that were present for duty (About 250 People). The data were collected through Osipow Occupational Stress Questionnaire, and then analyzed using the SPSS Statistics software (Ver. 22). The results show that the level of education has a significant relationship with most subscales of the questionnaire. Marital status and work experience had the lowest effect on job stress. Determining stress levels based on the classification related to the job group and the type of shift work system is similar, and these variables on the subscales affected the workload (p-value=0.001) and responsibility (p-value=0.000). Also, the results show that among the job groups, logistics (score: 197.4) and security (score: 177) have the highest and lowest tension, respectively. The results of this study showed that the effect of occupational variables on the defined ranges in the occupational stress questionnaire is different. These differences show that occupational stress has a dynamic nature, and any changes in the environmental dimensions can change the level of occupational stress.